ASSESSING THE IMPACT OF LOGO CHANGES ON THE BRAND EQUITY OF A HOTEL GROUP - Santos, M-C.; Marques, C.; Remédios, F. (European Marketing Academy Conference - EMAC 2017, 2017)
This study assesses the impact of logo changes in a corporate rebranding on the customers’ perception of brand experience, awareness, loyalty and perceived quality. How does rebranding contribute to the customer value is still scarcely analysed. This study contributes to the understanding of the rebranding evaluation from the customers’ perspective, by assessing the impact of a new logo arising from the corporate rebranding process of an international hotel group. After one year, customers compared their associations and attitudes towards the former and the current logo. Respondents reveal lower rebranding awareness. Brand equity levels and its constructs are enriched by the new logo especially due to its association with a prestigious brand that values customer’s time.